Effectiveness Of Chair Aerobics Vs Hydrotherapy on Functional Capacity in Middle-Aged Men - Zacharia, Amal.P.; Varadharajulu, G. (Journal of Neonatal Surgery, 2025)
Background: Functional capacity, which includes cardiovascular endurance, muscular strength, flexibility, and balance, is a crucial determinant of health and independence in aging populations. With increasing sedentary lifestyles and joint-related limitations, there is a growing need for accessible and joint-friendly exercise interventions. AIM OF THE STUDY To compare the effectiveness of chair aerobics and hydrotherapy in improving functional capacity—specifically cardiovascular endurance, muscular strength, flexibility, and balance—in middle-aged men over an eight-week intervention period. NEED FOR THE STUDY As the global population ages, maintaining functional independence is increasingly vital. Middle-aged men, particularly those leading sedentary lifestyles or dealing with musculoskeletal discomfort, are at risk of declining functional abilities. Conventional exercise routines may not be suitable for individuals with joint pain or reduced mobility. Hence, exploring alternative, low-impact exercise methods like chair aerobics and hydrotherapy is necessary to identify effective, scalable interventions. While both modalities are supported by prior research, direct comparative data in middle-aged men remain limited. This study addresses this gap, guiding clinical recommendations and community fitness programs. OBJECTIVE: This study aims to evaluate and compare the effectiveness of chair aerobics and hydrotherapy on functional capacity in middle-aged men over an eight-week intervention period. METHODS: A total of 62 middle-aged men were randomly assigned into two groups: Chair Aerobics (n=31) and Hydrotherapy (n=31). Both groups participated in 45-minute sessions, three times per week, for eight weeks. Functional capacity was assessed pre- and post-intervention using the 6-Minute Walk Test, 30-Second Chair Stand Test, Sit-and-Reach Test, and One-Leg Stand Test. RESULTS: Both groups demonstrated significant improvements across all parameters. Hydrotherapy showed greater gains in cardiovascular endurance (+16.5%), flexibility (+22.9%), and balance (+45.7%), whereas chair aerobics slightly outperformed hydrotherapy in muscular strength improvement (+50.0% vs +46.2%). CONCLUSION: While both modalities significantly enhance functional capacity, hydrotherapy offers broader benefits, particularly for individuals with joint-related limitations. Chair aerobics remains a highly effective alternative for populations with limited access to aquatic facilities.